Soil, plants and microorganisms in areas of Mn mining tailings 12 years after revegetation by different techniques - Silva, Elzane Freitas Leite (2019)
Although Mn is an essential element for plants, in excessive amounts in the soil it may reach toxic levels. For the success of the revegetation of areas with Mn mining tailings, it is necessary to consider, besides the best technique, the selection of plant species adapted to this condition. In addition, the evaluation of the microbial community of the soil and that associated with vegetation may indicate the progress of recovery. The objective of this study was to verify the occurrence of plant species growing at understory, plant and soil Mn concentrations, mycorrhizal colonization, communities of Mn-reducing and Mn-oxidizing bacteria and arbuscular mycorrhizal fungi (AMF), after revegetation by planting of seedlings and application of topsoil in the tailings deposition area, compared with an area under native forest and an unrevegeted site. Plant samples (at least three individuals/species), of bulk and rhizosphere soil were collected from the understory at revegetated locations and forest. The use of topsoil led to greater plant diversity. The high concentrations of Mn in the substrates did not affect the occurrence of vegetation in the understory and mycorrhizal colonization. The plant species established in the revegetated areas differed in relation to Mn concentration (471–27,842 mg kg -1 in leaves), Mn translocation factor (0.2–125.3) and mycorrhizal colonization rates (1– 35%). Four potential Mn, hyperaccumulator species were identified: Aparisthmium cordatum, Clidemia hirta, Socratea exorrhiza, and Vismia latifolia. In bulk soil Mn-reducing bacteria (0.2–23 x 10 4 CFU g -1 soil), Mn-oxidizing bacteria (0.02–1.3 x 10 4 CFU g -1 soil) and AMF spores (2–168) were detected. In the rhizospheric soil, no Mn-oxidizing bacteria were detected and the density of Mn-reducing bacteria varied greatly among the sampled plant species (0–40 x 10 4 CFU g -1 of soil). Isolates of rhizosphere Mn-reducing bacteria in the revegetated areas belong to the genera Bacillus, Cellulomonas and Paenibacillus. Nine AMF species were found in the studied areas, and Glomus was the predominant genus. All the microbial functional groups presented high resilience in relation to environmental modifications due to Mn mining and revegetation processes.